2015
DOI: 10.1007/s00701-015-2509-2
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Gamma Knife surgery safety and efficacy in the management of symptomatic benign confined cavernous sinus meningioma

Abstract: Gamma Knife surgery is a safe and effective option for the treatment of cavernous sinus meningioma not only as an adjuvant to surgery but also as an alternative to surgical removal in tumors confined mainly to the cavernous sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…For the predictors of tumor recurrence or progression, some studies revealed that increasing tumor volume was an independent predictor, which was also proved in our study. 10,16,29 In this study, many patients with intracranial meningiomas had low subjective acceptance of craniotomy; even though there were significant mass effect or neurological symptoms or signs, they preferred GKRS instead of craniotomy, which resulted in a high rate of large tumor (≥ 10 cm 3 ) in proportion at the time of GKRS, and reduced the treatment effect of GKRS in the cohort. In addition, a GKRS dose-plan defect may also influence local tumor control.…”
Section: Discussionmentioning
confidence: 76%
“…For the predictors of tumor recurrence or progression, some studies revealed that increasing tumor volume was an independent predictor, which was also proved in our study. 10,16,29 In this study, many patients with intracranial meningiomas had low subjective acceptance of craniotomy; even though there were significant mass effect or neurological symptoms or signs, they preferred GKRS instead of craniotomy, which resulted in a high rate of large tumor (≥ 10 cm 3 ) in proportion at the time of GKRS, and reduced the treatment effect of GKRS in the cohort. In addition, a GKRS dose-plan defect may also influence local tumor control.…”
Section: Discussionmentioning
confidence: 76%
“…15,17 More recently, other studies have reported a control of growth in 60%-96% of lesions at 2 years, 9,11 a decrease in volume by 20%, 5 and radiological progression after radiotherapy in 5%-11% of lesions. 5,7,15 In the present study, only 1 of 5 patients undergoing radiation therapy had a meningioma whose volume decreased (by 30%). The efficacy of radiotherapy on growth of these meningiomas must be consistent with the natural history of this entity, which has an unpredictable and irregular development.…”
Section: Radiotherapy Treatmentmentioning
confidence: 96%
“…12,21 It is noteworthy that the efficacy of radiotherapy on neuralgia may be explained not only by its oncological effects; radiation could directly act on CN V as thermocoagulation, thus resulting in partial denervation. 5,6,21,24,25 Survival without tumor progression (PFS) is variable according to studies, and ranges from 87% to 99% at 5 years and from 70% to 90% at 10 years. 15,17 More recently, other studies have reported a control of growth in 60%-96% of lesions at 2 years, 9,11 a decrease in volume by 20%, 5 and radiological progression after radiotherapy in 5%-11% of lesions.…”
Section: Radiotherapy Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…6,20,24,26,30,31,35 Hafez et al evaluated the results of stereotactic Gamma Knife radiosurgery in symptomatic benign CSMs and showed a tumor control rate of 96% at the 3-year follow-up period with a mean pretreatment tumor volume of 5.7 cm 3 (range 1.8-12.4 cm 3 ). 12 Maruyama et al treated their patients with radiosurgery alone when there was distance between tumors and the optic pathway or brainstem. They used a combination of surgery and radiosurgery for CSMs when the tumors were attached to or compressing the optic pathway and brainstem, were larger than 3 cm in diameter, and extended into the multiple cranial fossae.…”
Section: Treatment Strategy Of Primary Csmsmentioning
confidence: 99%